THE AMERICAN CIVIL WAR AND ITS REFLECTION IN LITERATURE - Baban, Dr. Naman (مجلة كلية الاداب, 1976)
These words of the 16th President of the United States of America exploded the already deteriorating situation created by the secession movement. In fact there were much more deep-rooted and fundamental causes behind the outbreak of the Secession War or the War of the Rebellion or the Civil War as 1 prefer to call it here, then putting the whole blame on Abraham Lincoln's opposition to slavery. Lincoln's paramount object was when he took office, to save the Union and not either to save or destroy slavery, (2) No doubt the issuance of the Emancipation Proclamation by the President was an act of boldness which gave a high moral tone to the cause of the North and hindered the Con federacy from establishing itself in the South.